Testing the continuum of delusional beliefs: an experimental study using virtual reality. - Freeman, D; Pugh, K; Vorontsova, N; Antley, A; Slater, M (2010)
A key problem in studying a hypothesized spectrum of severity of delusional ideation is determining that ideas are unfounded. The first objective was to use virtual reality to validate groups of individuals with low, moderate, and high levels of unfounded persecutory ideation. The second objective was to investigate, drawing upon a cognitive model of persecutory delusions, whether clinical and nonclinical paranoia are associated with similar causal factors. Three groups (low paranoia, high nonclinical paranoia, persecutory delusions) of 30 participants were recruited. Levels of paranoia were tested using virtual reality. The groups were compared on assessments of anxiety, worry, interpersonal sensitivity, depression, anomalous perceptual experiences, reasoning, and history of traumatic events. Virtual reality was found to cause no side effects. Persecutory ideation in virtual reality significantly differed across the groups. For the clear majority of the theoretical factors there were dose-response relationships with levels of paranoia. This is consistent with the idea of a spectrum of paranoia in the general population. Persecutory ideation is clearly present outside of clinical groups and there is consistency across the paranoia spectrum in associations with important theoretical variables.